2019
DOI: 10.1002/mrc.4860
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of fat crystallisation evaluated by low‐field NMR and small‐angle X‐ray scattering

Abstract: Low‐field time‐domain nuclear magnetic resonance (NMR; 20 MHz) is commonly used in the studies of fats in the form of solid fat content (SFC) measurements. However, it has the disadvantage of low sensitivity to small amounts of crystalline material (0.5%), thus often incorrectly determining crystallisation induction times. From spin–lattice relaxation rate measurements (R1) during the isothermal crystallisation measurements of cocoa butter between 0.01 and 10 MHz using fast field cycling NMR, we learnt previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…At this point, the importance of low-field TD-NMR is revealed due to its power to determine the solid–liquid ratio in foods and solid fat content determination . In various studies, the basic FID pulse sequence was generally utilized to define solid–liquid fractions and the crystallization behavior of food systems. ,,, Unlike the classical FID approach, liquid fractions (%) of Turkish delight samples were found by using the MSE sequence as explained in detail in the study of Grunin et al (2019). Similar to the liquid fractions, second moment values ( M 2 ) which are related to the crystallinity of the samples were also found by using the same pulse sequence again by referring to the same study, as indicated in the oncoming sections.…”
Section: Resultsmentioning
confidence: 99%
“…At this point, the importance of low-field TD-NMR is revealed due to its power to determine the solid–liquid ratio in foods and solid fat content determination . In various studies, the basic FID pulse sequence was generally utilized to define solid–liquid fractions and the crystallization behavior of food systems. ,,, Unlike the classical FID approach, liquid fractions (%) of Turkish delight samples were found by using the MSE sequence as explained in detail in the study of Grunin et al (2019). Similar to the liquid fractions, second moment values ( M 2 ) which are related to the crystallinity of the samples were also found by using the same pulse sequence again by referring to the same study, as indicated in the oncoming sections.…”
Section: Resultsmentioning
confidence: 99%
“…FFC NMR relaxometry versatility makes the technique quite useful in many fields. As an example, it has been applied to monitor food quality [25,26], traceability [27][28][29], conservation [30], and transformation [31][32][33][34][35][36][37]; to evaluate the physical chemical characteristics of systems useful for drug delivery [38]; to design new contrast agents to be used in diagnostic imaging techniques [39][40][41]; to explore tumor development [42]; to monitor environmental quality [18,43,44], and many other different applications that can be found elsewhere [45,46]. The present review paper is intended to explore the suitability in soil science of FFC NMR relaxometry.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been studied for linear polymers [10][11][12], as well as for cocoa butter [13] and fatty acids [14]. Those papers addressed questions regarding the role played by polymer selfand mutual-entanglement in the kinetics of memory effects.Recently, TAG crystallization has been studied [15][16][17][18]. Coexistence of solid and liquid state TAGs were reported [16].…”
Section: Introductionmentioning
confidence: 99%